A Roadmap to a Successful Exchange Rate Regime Transition: Takeaways from 6 African Transitions - Hamza Bouhali; Ahmed Dahbani; Brahim Dinar (Organizations and Markets in Emerging Economies, 2023)
This article investigates the role of monetary policies in the success of exchange rate regime transition and the mitigation of related risks. We adopted a comparative methodology for three types of regime switches using 3 GARCH family models and data from 6 African countries over two decades. Our main findings are that a gradual and well-prepared transition improves its outcome and allows the market more flexibility in absorbing domestic and external volatilities, even during a crisis. The results of this study will provide policymakers with a road map to succeed in the exchange rate regime transition and mitigate the inherent risks.